MODEL DISCOVERY LEARNING BERBANTUAN MEDIA GEOGEBRA DAN KEMAMPUAN LITERASI SPASIAL SISWA - Wardini, Sri Gusti; Kadir, Kadir; Dimyati, Ahmad (ALGORITMA: Journal of Mathematics Education, 2024)
AbstractSpatial literacy skills are essential to help students develop critical thinking skills. This study aims to analyze the effect of the Geogebra-assisted Discovery Learning model on spatial literacy skills. The research was conducted in one of the junior high schools in South Tangerang. The study used a quasi-experiment with a posttest-only control group design with randomization. The research sample was 25 experimental and control class students each. Data were collected using test instruments and analyzed using the Independent Sample t-test. The results revealed that the spatial literacy skills of students taught with the Geogebra-assisted Discovery Learning model were higher than those taught with conventional learning. The spatial literacy ability of experimental class students has the highest score on the visualization indicator and the lowest score on the reasoning indicator, while the control class students have the highest score on the communication indicator and the lowest score on the visualization indicator. The Discovery Learning model assisted by Geogebra affects students' spatial literacy skills. Abstrak Keterampilan literasi spasial memiliki peran yang sangat penting untuk membantu siswa dalam mengembangkan kemampuan berpikir kritis. Penelitian ini bertujuan untuk menganalisis pengaruh model Discovery Learning berbantuan Geogebra terhadap kemampuan literasi spasial. Penelitian dilaksanakan di salah satu SMP Swasta di Tangerang Selatan. Penelitian menggunakan kuasi eksperimen dengan rancangan Posttest only control group desain with randomization. Sampel penelitian sebanyak masing-masing  25 siswa kelas eksperimen dan kontrol. Data dikumpulkan dengan instrumen tes dan dianalisis menggunakan uji Independent Sampel t-Test. Hasil penelitian mengungkapkan kemampuan literasi spasial siswa yang diajarkan dengan model Discovery Learning berbantuan Geogebra lebih tinggi daripada yang diajarkan dengan pembelajaran konvensional. Kemampuan literasi spasial siswa kelas eksperimen memiliki skor tertinggi pada indikator visualisasi dan skor terendah pada indikator penalaran, sedangkan siswa kelas kontrol memiliki skor tertinggi pada indikator komunikasi dan skor terendah pada indikator visualisasi. Model Discovery Learning berbantuan Geogebra berpengaruh terhadap kemampuan literasi spasial siswa.